Transparency in surgical randomized clinical trials: cross-sectional observational study. Issue 5 (15th August 2020) - Helliwell, J A; Shelton, B; Mahmood, H; Blanco-Colino, R; Fitzgerald, J E; Harrison, E M; Bhangu, A; Chapman, S J
Abstract: Background: RCTs provide the scientific basis upon which treatment decisions are made. To facilitate critical review, it is important that methods and results are reported transparently. The aim of this study was to explore transparency in surgical RCTs with respect to trial registration, disclosure of funding sources, declarations of investigator conflicts and data-sharing. Methods: This was a cross-sectional review of published surgical RCTs. Ten high-impact journals were searched systematically for RCTs published in years 2009, 2012, 2015 and 2018. Four domains of transparency were explored: trial registration, disclosure of funding, disclosure of investigator conflicts, and a statement relating to data-sharing. Results: Of 611 RCTs, 475 were eligible for analysis. Some 397 RCTs (83.6 per cent) were registered on a trial database, of which 190 (47·9 per cent) had been registered prospectively. Prospective registration increased over time (26 per cent in 2009, 33·0 per cent in 2012, 54 per cent in 2015, and 72·7 per cent in 2018). Funding disclosure was present in 55·0, 65·0, 69·4 and 75·4 per cent of manuscripts respectively. Conflict of interest disclosure was present in 49·5, 89·1, 94·6 and 98·3 per cent of manuscripts across the same time periods. Data-sharing statements were present in only 15 RCTs (3·2 per cent), 11 of which were published in 2018. Conclusion: Trial registration, disclosure of funding and disclosure of investigator conflicts in surgical RCTs have improved markedly over the past 10 years. Disclosure of data-sharing plans is exceptionally low. This may contribute to research waste and represents a target for improvement. Graphical Abstract: This cross-sectional observational study explored transparency of surgical RCTs. It found that trial registration, presence of funding statements and disclosure of personal conflicts improved rapidly over the past 10 years. In contrast, disclosure of data-sharing plans remains exceptionally low; this may contribute to research waste and represents an essential target for improvement. Standards improving but data sharing problematic.